Child with cytomegalovirus associated acute demyelinating encephalomyelitis: a case report (Bangladesh Journal of Medical Science, 2022)
Cytomegalovirus (CMV) is a common virus that causes mild, self-limiting illness in immunocompetent individuals. However, CMV is also frequently associated with acute demyelinating encephalomyelitis (ADEM), which is an uncommon monophasic idiopathic inflammatory demyelinating disease. It affects both children and adults. This is a case of unfortunate boy with CMV infection which was complicated with ADEM. Prompt diagnosis and aggressive treatment had provided a good outcome in this patient.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 749-753